Adipose-derived stem cells inhibit dermal fibroblast growth and induce apoptosis in keloids through the arachidonic acid-derived cyclooxygenase-2/prostaglandin E2 cascade by paracrine. Issue 1 (11th September 2021) - Yang, Jinxiu; Li, Shiyi; He, Leren; Chen, Minliang
Abstract: Background: The clinical features of keloids consist of aberrant proliferation, secretion, differentiation and apoptosis of keloid dermis-derived fibroblasts (KFBs). Notably, the apoptosis rate of KFBs is lower than the proliferation rate. Though the anti-fibrotic effect of adipose-derived stem cells (ADSCs) on keloids has become a hot topic of research, the exact anti-fibrotic mechanism of the paracrine effect remains unclear. This study aimed to find out how the conditioned medium of ADSCs (ADSC-CM) exerts an anti-fibrotic effect in KFBs. Methods: KFBs and ADSCs were extracted and cultured. Then, ADSC-CM was prepared. Whether ADSC-CM could inhibit KFB growth and induce apoptosis was verified by the use of a cell counting kit-8, an 5-Ethynyl-2-deoxyuridine (Edu) kit and flow cytometry. The expressions of cyclooxygenase-1 (COX-1), COX-2, caspase 3 and B-cell lymphoma-2 (Bcl-2) in ADSC-CM-cultured KFBs were tested by real-time PCR and western blotting. To clarify the role of COX-2 in ADSC-CM-induced KFB apoptosis, a specific COX-2 inhibitor, celecoxib, was applied to KFBs cultured in ADSC-CM. Moreover, we tested the production of arachidonic acid (AA) and prostaglandin E2 (PGE2) by ELISA. Then, we established a keloid transplantation model in a nude mouse to validate the therapeutic effect in vivo . Results: The proliferation ability of KFBs cultured in ADSC-CM was found to be weakened and apoptosis was significantly increased. Caspase 3 expression was significantly upregulated and Bcl-2 was downregulated in ADSC-CM-cultured KFBs. Furthermore, ADSC-CM strikingly elevated COX-2 mRNA and protein expressions, but COX-1 expression was unaltered. COX-2 inhibitors reduced ADSC-CM-induced apoptosis. Additionally, COX-2 inhibition blocked the elevation of caspase 3 and reversed the decrease in Bcl-2 expression. ADSC-CM increased PGE2 levels by 1.5-fold and this effect was restrained by COX-2 inhibition. In the nude mouse model, expressions of AA, COX-2 and PGE2 were higher in the translated keloid tissues after ADSC-CM injection than in the controls. Conclusions: We showed activation of the COX-2/PGE2 cascade in KFBs in response to ADSC-CM. By employing a specific COX-2 inhibitor, COX-2/PGE2 cascade activation played a crucial role in mediating the ADSC-CM-induced KFB apoptosis and anti-proliferation effects.